Behavioural responses of eel (Anguilla anguilla) approaching a large pumping station with trash rack using an acoustic camera (DIDSON). (5th April 2020) - van Keeken, Olvin Alior; van Hal, Ralf; Volken Winter, Hendrik; Tulp, Ingrid; Griffioen, Arie Benjamin
Abstract: European eel, Anguilla anguilla L., migrating to the sea encounter many man‐made structures that can hamper and delay migration or induce mortality. Studying small‐scale behavioural movements in front of these man‐made structures could provide insight in further mitigating adverse effects. The behaviour of eel approaching a trash rack in front of a large pumping station was investigated using a dual‐frequency identification sonar (DIDSON). Eels approaching the trash rack swam through the rack (40.5%) but also showed turning behaviour at (44.7%) or in front of the rack (14.7%). Eels approaching the rack had varying body positions, predominantly head or tail first, but also curled up into a ball or drifted sideways. After turning in front or at the trash rack, eels showed upstream and downwards swimming towards the canal bottom. The results suggest a stepwise response to potential cues, when firstly the body position is changed in such a way that secondly, later on, enhances eventual fast upstream escapement when perceived necessary. Implications for management of these behavioural observations are discussed.